Comparative Characteristics of Electrolyte Solutions Using Electrical Impedance Spectroscopy Method - Fathia D.S, Adinda Fajar Mila; Sugianto, Wahyu; Setiana, Mira (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Electrolyte solutions can conduct electric current and help maintain balance in the human body. This study compares the electrical impedance characteristics of various electrolyte solutions using the Electrical Impedance Spectroscopy (EIS) method. Three types of electrolyte solutions were tested: NaCl solution, Ringer’s Lactate (RL) solution, and Simulated Body Fluid (SBF) solution with concentration variations of 20%, 40%, 60%, 80%, and 100%. Measurements were conducted over a frequency range from 1 Hz to 1 MHz to compare electrolyte solutions using a frequency of 10 kHz with an electric current of 50 μA. At a frequency of 10 kHz, a comparison of the three types of electrolyte solutions with concentration variations from 20% to 100% was made. The measurement result showed that the NaCl solution had an impedance value of 200Ω to 900Ω at high frequencies. The Ringer’s Lactate (RL) solution exhibited impedance variations with impedance values ranging from 800Ω to 300Ω, which is more complex due to the other hand, the Simulated Body Fluid (SBF) solution demonstrated impedance stability at high frequencies with impedance values ranging from 400Ω to 200Ω, indicating its electrical properties suitability with human body conditions. Each electrolyte solution has its characteristics in impedance values at a frequency of 10 kHz, which allows for comparing the three types of electrolyte solutions. For further research, additional studies could include impedance characteristics of electrolyte solutions to broaden understanding of their electrical properties, considering variations in frequency and current conditions to optimise impedance characteristic measurements for various electrolyte solutions.